1991
DOI: 10.1182/blood.v78.12.3168.bloodjournal78123168
|View full text |Cite
|
Sign up to set email alerts
|

Aphidicolin, an inhibitor of DNA replication, blocks the TPA-induced differentiation of a human megakaryoblastic cell line, MEG-O1

Abstract: The commitment process of a human megakaryoblastic cell line (MEG-O1) induced with phorbol ester, TPA, was investigated with special reference to glycoprotein (GP) IIb/IIIa expression, multinuclear formation, and DNA replication. TPA (10(-7) mol/L) completely inhibited cellular division in MEG-O1, but did not suppress de novo DNA synthesis. Two days' culture with 10(-7) mol/L TPA was sufficient for MEG-O1 cells to initiate an irreversible commitment process. These cells could not resume cell growth and express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1995
1995
1998
1998

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The long incubation time of 48 h required for maximal effect indicates that cell division may be a prerequisite for activin-A action. Indeed, aphidicolin, an inhibitor of DNA polymerase a [31] and thereby of DNA replication, also blocked the activin-A-dependent induction, suggesting cell-division-dependent differentiation of the J774.1 cells as a cause for the increase in cyclooxygenase activity, in agreement with the slow time response ( Fig. 3).…”
Section: Resultssupporting
confidence: 68%
“…The long incubation time of 48 h required for maximal effect indicates that cell division may be a prerequisite for activin-A action. Indeed, aphidicolin, an inhibitor of DNA polymerase a [31] and thereby of DNA replication, also blocked the activin-A-dependent induction, suggesting cell-division-dependent differentiation of the J774.1 cells as a cause for the increase in cyclooxygenase activity, in agreement with the slow time response ( Fig. 3).…”
Section: Resultssupporting
confidence: 68%
“…The clonal human megakaryoblastic leukaemia cell line MEG‐01 and its subline MEG‐01s, established by Ogura et al (1985 , 1988), display phenotypic properties that closely resemble those of megakaryoblasts but not other blood cell lineages. These properties demonstrate increased expression after treatment of the cells with phorboldiester, TPA ( Murate et al , 1991 ). The cell lines also release particles identified by a characteristic marginal microtubule and by the localization of platelet‐specific glycoprotein (GPIIb/IIIa) in the plasma membrane ( Takeuchi et al , 1991 , 1995).…”
mentioning
confidence: 99%
“…K‐252a induced Meg‐J cells to form polyploid cells, which were accompanied by the morphological differentiation and increases in the levels of GPIIb/IIIa and GPIb expression. It has been suggested that DNA synthesis is a prerequisite not only for polyploidization but also for the expression of megakaryocytic markers such as GPs in TPA‐treated megakaryocytic differentiation ( Murata et al , 1991 , 1993; Yoshino et al , 1996 ). In our system, such DNA synthesis without cell division may also have induced increased levels of megakaryocytic markers.…”
Section: Discussionmentioning
confidence: 99%
“…Phorbol‐12‐myristate‐13‐acetate (TPA) was reported to induce megakaryocytic differentiation in some megakaryocytic cell lines. However, its ability to induce polyploidization was not sufficient to allow analysis of the mechanism of polyploidization ( Ogura et al , 1988 ; Long et al , 1990 ; Greenberg et al , 1988 ; Murata et al , 1991 ). K‐252a, an indolocarbasole derivative protein kinase inhibitor isolated from the culture broth of Nocardiosis SP ( Kase et al , 1986 , 1987) causes polyploidization without intervening mitosis in various cultured cell lines ( Usui et al , 1991 ).…”
mentioning
confidence: 99%